Dynamics and controls of CO2 and CH4 emissions in the wetland of a montane permafrost region, northeast China. (December 2015) - Liu, Xia; Guo, Yuedong; Hu, Haiqing; Sun, Chengkun; Zhao, Xikuan; Wei, Changlei
Abstract: To quantify the fluxes and examine the controls on greenhouse gas emissions from the permafrost marshes where the fate of the large quantity of soil organic carbon remains poorly understood, we measured carbon dioxide (CO2 ) and methane (CH4 ) emissions in the northern region of the Great Xing'an Mountains, northeast China, in the thawing seasons of 2011 and 2012. The mean CO2 and CH4 fluxes from the marshes were estimated at 403.47 and 0.14 mg m −2 h −1 on average during the two years. Soil temperature was determined as the primary control on the seasonal greenhouse gas emissions during the growing period. The Q10 values, calculated from the exponential regression between soil temperature and CO2 emissions, suggest that the sensitivity of CO2 flux to climate warming has a high spatially variability in the study area. Absorption of atmospheric CH4 was seasonally detected at the sites with lower water table, which confirms the potential of the natural marshes as CH4 sink when water table goes down due to climate change. When viewed from the ecosystem scale, the mean annual water table level and aboveground primary production were deemed as the dominant influencing factors for the mean annual fluxes, which suggests that there were different controls on the gas emissions at different spatial scales. Therefore, the primary controls of the CO2 and CH4 emissions at different spatial scales need to be surveyed in more detail when focusing on the future alteration of greenhouse gas emissions from permafrost marshes due to climate warming. Highlights: Soil temperature controls the seasonal CO2 /CH4 emissions from permafrost marshes. The sensitivity of CO2 flux to soil temperature has a high spatially variability. There are different controls on the gas emissions at different spatial scales.